STUDENTS’ PERCEPTION OF KOREAN WAVE IN THEIR GENERAL KNOWLEDGE OF ENGLISH - Kurniawan, Nurhadi; Afrianto, Afrianto; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is aimed to acquired data of students’ perception of Korean Wave in their general knowledge of English listening, reading, and vocabulary as perceived by them. this research was conducted with survey and analysed descriptively. The broad area of survey research encompasses any measurement procedures that involve asking questions of respondents. This method was used to get a clear picture, and to describe students' perception about the Korean Wave in improving students’ general knowledge of English. The practical part of this study is conducted on junior and senior high school students who in Pekanbaru from which The sample includes fans who are keeping up with K-pop and K-drama for more than one year in order to detect traits that are more influential. Moreover, 100 participants responded to the questionnaire used as a research instrument for achieving the goal of this study. The result in general that students in Pekanbaru have a positive perception of Korean Wave in improving their English. It is also found that Korean Wave has motivated them to learn English by themselves. Based on the research findings, it is showed that Korean Wave give positive perceptive on students in their general knowledge of English and can be used by teachers to increase students’ English.Key Words : Perception, Korean Wave, English General Knowledge